Examining school boards' chaotic leadership style in relation to teachers' job satisfaction and emotional exhaustion. (October 2022) - Haerens, Leen; Matos, Lennia; Koc, Andrea; Benita, Moti; Abos, Angel
Abstract: School leaders adopt a chaotic style when they abdicate their responsibilities by being unavailable, passive, unpredictable and permissive. Surprisingly, this dark side of leaders' style has been largely ignored in contemporary research. In a sample of 205 teachers, this cross-sectional study revealed that, an autonomy-supportive style positively related to job satisfaction via need satisfaction, while a chaotic style positively related to emotional exhaustion via need frustration. Latent profile analyses revealed four profiles: highly autonomy-supportive (35%), moderate on both styles (41%), moderately chaotic (18%), and highly chaotic (6%). A group that was low on both styles was not found. Highlights: The bright and dark side of school leaders' style is examined. A chaotic style relates to emotional-exhaustion via need frustration. Teachers who perceived high levels of autonomy-support and low levels of chaos displayed the most optimal outcomes. When being autonomy-supportive, school boards endeavor the challenge not to become too passive or permissive.